Sourcing arrangement of internal audit services: does it matter to the external auditors? - Mustapha, Mazlina; Lee, Yip Kwan (Inderscience Publishers, 2020)
Internal audit is a crucial monitoring mechanism which assists management in evaluating the effectiveness of the organisational operations. This service can be obtained internally or externally by outsourcing the service to public accounting firms. Due to the importance of the function, this study aims to examine whether the sourcing arrangement of this function would influence the external auditors reliance on the work of internal audit in the audit processes. Questionnaires were randomly distributed to 100 external auditors in Klang Valley. The results indicate that external auditors would significantly rely more on the work of out-sourced internal auditors compared to in-house internal auditors, especially when the inherent risk is high. The level of internal auditors' compliance with relevant professional standards is another crucial factor influencing the external auditors' reliance on their work. This study provides information to the regulators and policy makers in Malaysia about the factors that are important to the external auditors in the auditing processes.